Food safety assessment and challenges along small-scale pig systems in Vietnam - Unger, Fred; Hung Nguyen-Viet; Sinh Dang Xuan; Phuc Pham Duc; Pham Van Hung; Lapar, Ma. Lucila; Marshall, Karen; Duong Van Nhiem; Makita, K.; Grace, Delia (International Livestock Research Institute, 2016)
Food borne diseases (FBD) are an increasing global public health concern with estimated 1 in 10 people falling ill every year from eating contaminated food causing 420,000 deaths. Diarrheal diseases accounted for more than half of the global burden with children at especial risk (WHO 2015). Evidence on FBD in low and middle income countries, including Vietnam, is still limited but the risk is considered to be higher than in high income countries due to poor hygiene, inadequate food production and storage, risky consumption habits, and weak legislation and enforcement. For Vietnam, pork is an important component of the diet and accounts for more than 70% of meat consumed: most (84%) is supplied by small and medium scale farmers. Recent ILRI studies have demonstrated strong preferences of Vietnamese consumers for fresh, un-chilled pork sold at conventional wet markets but also increasing concerns over food safety have been expressed by urban consumers. Existing food safety studies along the pig sector have focused on assessment of hazards (mainly Salmonella) at a specific actor of the pork chain while farm to fork approaches or studies measuring the impact of hazards to human are limited. Since 2012 ILRI has implemented specific studies assessing food safety issues including zoonoses along pig value chains in selected regions of Vietnam. This included risk assessments of food safety hazards in pork such as Salmonella along a more peri-urban value chain with mainly exotic pigs or their crosses (Hung Yen province). In addition, we assessed the presence of two major zoonoses (trichinellosis and cysticercosis) in a rural indigenous pig value chain in the Central Highlands of Vietnam. Results for Hung Yen show a high presence of biological hazards (e.g. 43% pork cuts at market are Salmonella contaminated). Key challenges include poor slaughter and meat handling hygiene (eg. floor slaughter) aligned with low awareness on related health risks among interviewed actors. Another challenge is to identify feasible incentives to motivate change of behavior and practice of actors. For the native pig system (Central Highlands) sporadic infections with trichinellosis and cysticercosis were found. Key challenges include here predominant risky farm management practices (free roaming of pigs) but also very low awareness and knowledge on zoonoses of native pig producers who are often members of poor ethnic minorities.